If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x^10=(3x.)+(3x.)=
We move all terms to the left:
3x^10-((3x.)+(3x.))=0
We do not support expression: x^10
| -5.5x=16.5 | | $3.05-m=$2.98 | | 65x=2,535 | | 4(t-3)+12=-4t | | 3 | | 3 | | 3 | | 2n^2=7=-15 | | 1/3x-4+x=2/3(x-9) | | 84x=3203-3154 | | 1/6p+8=-1/3=14 | | 8t-3t+6=5(t-1) | | 29q=87 | | 1.33+b=-5.66 | | 12/100=x/36 | | 12=x+ | | 1.2+b=0.5 | | 5(4-x)=2(x+3) | | 6/5+x=1/2 | | 2x-2-8x=-6x-12+10 | | 4x-9=-10+2x+7 | | 5-3x=12x-10 | | l(4)=2l+2(4) | | 1x=-1.3 | | 2(2.5+1.5x)=3x+5 | | 4.9x^2-40.98x-7=0 | | 3.2b+5=-26 | | 5t+7=-3t+t | | F(n)=61-3 | | -1.5x-9=15 | | 4/3=2a+6/5a-3 | | 2x+18-4x=25 |